TEMPORARY MALOCCLUSION TREATMENT AT MIX DENTITION PERIOD (PERAWATAN MALOKLUSI SEMENTARA PADA PERIODE GIGI CAMPURAN) - Hillda Herawati; Syifa Sahaliya (Fakultas Kedokteran Gigi Unjani, 2022)
The growth and development of primary teeth in children need attention from an early age because primary teeth have an important role in mastication, and speech development and provide a place for the eruption of their permanent teeth. Malocclusion is a condition of dentofacial disharmony that can interfere with mastication, swallowing, speech, and facial alignment. Case Report: A mother and her daughter, 9-year-old, came with the complaint that her daughter's teeth look crowding. The left mandibular canine looks more backward because previously, there were primary teeth that had accumulated and had been extracted, while the two maxillary canines looked crooked. The patient and parents were educated to push the teeth with the tongue daily as often as possible. After a 4-month evaluation, the tooth was in the proper dental arch. However, fixed orthodontic treatment was required when all of the patient's teeth fully erupted to correct the patient's maxillary malocclusion. Conclusion: The growth and development of primary teeth in children need attention from an early age. Malocclusions that are found early, can be treated early to prevent the severity of the malocclusion from increasing. DOI : 10.54052/jhds.sd22.p167-176